Underweight among preschool children as an acute consequence of household food insecurity in Occidental Mindoro - Mustaqim, Wendy A.; Bullecer, Ernani R. (2020)
Across the globe, millions of people are experiencing poverty that further deteriorates the food security of the population. In the Philippines alone, millions of children were suffering from inadequate food intake and undernourishment. Dilemmas concerning household food insecurity continuously impose threats in the growth of children. This study aimed to determine the association of household food insecurity with underweight among preschool children in Occidental Mindoro. Specifically, it estimates the prevalence of household food insecurity, less diverse diet, and underweight among preschool children. This study utilized analytical, cross-sectional design whereas three multi-stage, systematic simple random sampling design was used to select the 480 preschool children. The Radimer-Cornell tool and child growth standards were used to assess household food security status and weight-for-age status of children, respectively. Multiple logistic regression was used to answer the major objective. The prevalence of household food insecurity was recorded at 51.0% (95% CI: 46.6?55.5%). Meanwhile, prevalence of less diverse diet among preschool children was 31.7% (95% CI: 27.5?35.8%) and underweight was 30.2% (95% CI: 26.3?34.6%). After controlling the confounding effect of a less diverse diet, it was found that the odds of being underweight among preschool children were seven times higher if a household was food insecure (OR: 7.1, 95% CI: 4.2?11.8). Prevalence of household food insecurity, less diverse diet, and underweight among preschool children were found to be high in Occidental Mindoro. After controlling the effect of a less diverse diet, the odds of having an underweight child were 86% lower if the household was food secure. (Author's abstract)